Analisis Ion Magnesium (Mg²⁺) dengan Kromatografi menggunakan Silika Gel-GPTMS Termodifikasi Sulfonat sebagai Fasa Diam - Hellena Ditasya; Budhi Oktavia (MASALIQ, 2025)
The limited number of studies on the use of modified silica gel as a stationary phase in ion chromatography, particularly for magnesium ion (Mg²⁺) analysis, forms the basis of this research. The primary objective is to modify silica gel with 3-glycidyloxypropyltrimethoxysilane (GPTMS) and sulfonate groups to develop a novel stationary phase selective for Mg²⁺ analysis. A quantitative experimental method was employed using Mg²⁺ samples at concentrations of 100, 200, and 300 ppm. Analysis was conducted using High-Performance Liquid Chromatography (HPLC) with two types of eluents: tartaric acid (0.05 M, 0.07 M, 0.09 M) and methanesulfonic acid (0.01 M). The results show that tartaric acid failed to produce distinct chromatographic peaks at all concentrations, likely due to its low ionic strength, which caused Mg²⁺ ions to remain strongly bound to the stationary phase, resulting in signal-to-noise (S/N) ratios below the quantification limit. In contrast, methanesulfonic acid generated sharp peaks with a retention time of 7.47 minutes, peak height of 53.68 mAU, and peak area of 4.42, indicating effective Mg²⁺ detection. These findings suggest that the high ionic strength of methanesulfonic acid makes it a more suitable eluent for silica gel GPTMS-sulfonate-based ion-exchange chromatography systems. The main conclusion of this study is that GPTMS-sulfonate silica gel exhibits high potential as a stationary phase for Mg²⁺ ion analysis using ion chromatography, with optimal performance when methanesulfonic acid is used as the eluent.